Layʻ tī Cha rā toʻ Bhu rāʺ krīʺ cī raṅʻ toʻ mū ʼapʻ so Pāramī dīpanī - Ñāṇa, Ledi Cha rā toʻ, 1846 or 7-1923 or 4. (Haṃsāvatī Piṭakatʻ Puṃ nhipʻ tuikʻ, 1955)
Perfection and virtues (paramitas) in Buddhist literature.